Mindful reflexivity: Unpacking the process of transformative learning in mindfulness and discernment. Issue 2 (April 2020) - Vu, Mai Chi; Burton, Nicholas
Can spiritual practice encourage transformative learning? In this article, we unpack how spiritual practices from the Buddhist tradition—mindfulness—and the Quaker tradition—discernment—encourage the attainment of moral reflexivity and the capacity to transform self in individual and relational organizational contexts, respectively. We also show how moral reflexivity and self-transformation are mutually reinforcing and promote a transformational cycle of management learning. We propose that "mindful reflexivity", a foundational model of spiritually informed moral reflexivity, can contribute to new ways of management learning through its context sensitivity and ethical orientation to foster the kinds of reflexivity needed for responsible management. Our article concludes with implications for management learning theory and practice, and we offer pathways for future research.